Intertextuality and Late Antiquity in Michael E. Pregill's Interpretation of the Worship of the Golden Calf in Surah Thāhā: 83-97 - Nur Afra Afifah Amani Amatullah; Nur Laili Nabilah Nazahah Najiyah; Inayah Rohmaniyah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
Michael E. Pregill argues that the story in Surah Thāhā: 83-97 reflects an interpretation trend of a story in the Bible, thriving among Jews and Christians in Late Antiquity, about Israelites who worshipped the golden calf. Pergill also argues about the intertextuality between the Qur’an and Bible. This study aims to comprehensively examine Pregill’s interpretation of Surah Thāhā: 83-97 as it responds to the differences in detailed stories of golden calf worship in the Qur’an and Bible and various interpretations of Al-Sāmīrī. Primary data of this qualitative study included a book entitled The Golden Calf between Bible and Qur’an: Scripture, Polemic, and Exegesis from Late Antiquity to Islam. Relevant data were collected and analyzed through data condensation, data display, and conclusion drawing/verification. According to Pregill, Al-Sāmīrī was a literary work of the Qur’an using biblical materials; then, Qur’an applied it to Harun’s name and emphasized his role as the Israelites’ guardian. The intertextuality between Qur’an and Bible was perceived from the possibility of using Ethiopic Bible materials to retell the event. In response to interpretation trends focusing on covenant, priesthood, and idolatry themes, Pregill argues that the Qur’an has affirmed Harun’s position as the Priest under Moses the Prophet.